Sequências Ofiolíticas Internas da Zona de Ossa-Morena: implicações geodinâmicas na evolução da Cadeia Varisca Ibérica - Pedro, Jorge (2005)
The Internal Ophiolitic Sequences correspond to allochthonous oceanic crust fragments that outcrop near the SW boundary of the Ossa-Morena Zone (Evora-Beja Domain), in an internal position relative to the Beja-Acebuches Ophiolitic Complex. The Internal Ophiolitic Sequences occur as tectonic imbrications or klippen, in the Moura Phyllonitic Complex. Despite deformation and metamorphism (greenschist/amphibolite facies), they still preserve a typical ophiolitic internal stratigraphy identical to the one described for many LOT (“Lherzolitic Ophiolite Type”) ophiolites. Geochemical data indicates that the Internal Ophiolitic Sequences have variable tholeiitic chemistry, transitional between N-MORB and E-MORB. Petrogenetic modelling suggests that the observed geochemical variations reflect both mantle source heterogeneity and partial melting processes. The Internal Ophiolitic Sequences geochemistry indicates that their igneous protholites formed in an anorogenic tectonomagmatic environment, like the ocean ridge basins, without any influence of orogenic components related to subduction mechanisms. These features contrast markedly with those reported for the Beja-Acebuches Ophiolitic Complex, which have been interpreted as representing oceanic crust generated in a “back-arc” setting,. Thus, supporting the existence of two distinct oceanic basins (ocean ridge and back-arc) during the geodynamical evolution of the SW Iberian Variscan Chain. Therefore, the Internal Ophiolitic Sequences in the Ossa-Morena Zone reflect the early oceanization events during the Variscan Orogeny.